Efek Pengasapan Menggunakan Bahan Nabati terhadap Viabilitas dan Pertumbuhan Awal Benih Jagung (Zea Mays L) Lokal Timor - Bano, Adriana Ernawati; Tefa, Anna; Nino, Jefrianus (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2023)
Corn is a food that is easily accepted, people, because it is a tradisional food in NTT and also as a staple food. Thys study aimed to determine the germination and early growth of local Timor cornseeds that were smoked using vegetable materials. This research was carried out in December 2021 at the Laboratory, Faculty of Agriculture, University of Timor, Kefamenanu. This research uses Completely Randomized Design (CRD) single factor : smoking from vegetable ingredients Kusambi (Ku), krinyu leaf (Kr), Gringsingan (Gr) the results of this study show the highest value namely the parameter germination capacity (96,67%), maximum growt potential (86,36%), growt speed (15,94%), vigor index (10,67%), and dry weight of sprouts were normal (8,29 gram). Initial growth parameters with the value height (39,13cm), number of leaves (4), stem diameter (0,55 mm).